2022
DOI: 10.1186/s12889-022-13017-y
|View full text |Cite
|
Sign up to set email alerts
|

The co-management of tuberculosis-diabetes co-morbidities in Indonesia under the National Tuberculosis Control Program: results from a cross-sectional study from 2017 to 2019

Abstract: Background Indonesia suffers from a high burden of tuberculosis (TB) and diabetes (DM). The government initiated national TB-DM co-management activities under the National TB Control Program in 2017. This study investigates the detection and treatment outcomes of TB-DM in Jakarta after implementing these activities, and identifies the main factors associated with these outcomes. Methods A cross-sectional study was conducted using TB registry data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Additionally, the current study found a favorable relationship between tobacco usage and smoking for TB among adults (Khaliq et al, 2015). One of the highest smoking rates in the world is found in Indonesia (Jiang et al, 2022). Therefore, the task is not just to reduce the number of smokers but also to reduce the number of TB cases among smokers.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Additionally, the current study found a favorable relationship between tobacco usage and smoking for TB among adults (Khaliq et al, 2015). One of the highest smoking rates in the world is found in Indonesia (Jiang et al, 2022). Therefore, the task is not just to reduce the number of smokers but also to reduce the number of TB cases among smokers.…”
Section: Discussionmentioning
confidence: 49%
“…To help Indonesia reach its 2030 TB elimination target, the central and local governments' roles in TB control must be increased. One of them is the health reform, which highlights the value of sustainable implementation in Indonesia at the regional level (Nindrea et al, 2020;Jiang et al, 2022;Nindrea et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations